2021
DOI: 10.1039/d1an00660f
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxazine pseudonucleotides in DNA i-motifs allow precise profiling of small molecule binders by fluorescence monitoring

Abstract: The lack of HTS techniques for small molecules that stabilize DNA iMs limits their development as perspective drug candidates. Here we showed that fluorescence monitoring for probing effects of ligands...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…15,16 The identification and evaluation of i-DNA ligands are hampered by the lack of robust, uniform assays such as FRET-melting and FID assay that became routine in the field of G4 ligand. In fact, these methods have strong biases and provide untrustworthy results with i-DNA, as evidenced in recent publications, 17,18 prohibiting direct comparison of the ligands described by different groups. In this context, we have previously assembled two peptide-DNA conjugates that form i-motif structures, 19,20 with one of them, namely conjugate 2 (Fig.…”
mentioning
confidence: 99%
“…15,16 The identification and evaluation of i-DNA ligands are hampered by the lack of robust, uniform assays such as FRET-melting and FID assay that became routine in the field of G4 ligand. In fact, these methods have strong biases and provide untrustworthy results with i-DNA, as evidenced in recent publications, 17,18 prohibiting direct comparison of the ligands described by different groups. In this context, we have previously assembled two peptide-DNA conjugates that form i-motif structures, 19,20 with one of them, namely conjugate 2 (Fig.…”
mentioning
confidence: 99%
“…In the conditions of that study (50 mM Na cacodylate buffer, pH 5.8), the relative fluorescence variation at 520 nm (i.e., FAM emission) was less than 10%, and an equilibrium dissociation constant K D of around 490 nM was determined. However, it has been more recently shown that fluorophores typically used in the FRET assay may introduce strong biases into ligand interactions with i-DNA [ 29 , 30 ], namely by direct fluorophore–ligand interactions. Moreover, the authors have performed CD melting experiments and observed a very low effect of the ligand on thermal stability of bcl-2 i-DNA (∆ T m = 1 °C), which appears rather surprising considering the reported sub-micromolar affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the structure was optimized using Powell’s method. Calculations of the partial charges in the modified loops and 80 ns molecular dynamics (MD) simulations were performed according to published protocols …”
Section: Methodsmentioning
confidence: 99%
“…Calculations of the partial charges in the modified loops and 80 ns molecular dynamics (MD) simulations were performed according to published protocols. 42 Nuclease Hydrolysis. For endonuclease hydrolysis assays, S1 endonuclease (Thermo Fisher Scientific) was added to a 6 μM ODN solution in the S1 reaction buffer (50 mM sodium acetate, pH 4.5, 280 mM NaCl, and 45 mM ZnSO 4 ) to a final S1 concentration of 0.2 u/μL.…”
Section: Design and Synthesis Of Labeled Native And Modifiedmentioning
confidence: 99%